PENGARUH KINERJA SOSIAL DAN KINERJA LINGKUNGAN TERHADAP KINERJA KEUANGAN - Ahmad Rosyid (JURNAL PENELITIAN, 2015)
This study aimed to examine the effect of social and environmental performance disclosure on financial performance in companies listed on the Stock Exchange under the energy, mining, and infrastructure industry sectors during 2010–2013. Using a multiple regression method, the results show that environmental and social performance simultaneously affect financial performance, while partially none of the independent variables significantly affect the dependent variable. However, the positive direction of their relationship is consistent with the theory—that the better the environmental and social performance, the better the financial performance.